MELINDUNGI KEBERLANJUTAN IOT EDUKASI KEAMANAN BAGI SISWA SMAN 1 JASINGA - Pebrianto, Juri; Arya Adhyaksa Waskita (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This PKM highlights the issue of Internet of Things (IoT) security in everyday life, especially among the students of IT Club SMAN 1 Jasinga. Involving a series of workshops, practical training, discussion sessions, and the creation of educational materials, the programme aimed to improve IoT security understanding and skills. The results include increased student knowledge, practical skills in securing devices and networks, and a heightened awareness of the importance of IoT security. The educational materials produced can be accessed by students and the community, while the positive contributions of the programme are expected to be published in a service journal. In addition, this PKM includes service to partners in the field of productive economy, with a focus on production evaluation, modern agriculture training, measurement and monitoring of production results, as well as identification of management problems and management training. The rationale of this PKM is to provide an in-depth understanding of IoT security, improve students' readiness to face the complexity of the digital world, and create change agents who share knowledge in the community. The PKM objectives involved understanding, practical skills, awareness, and creation of educational materials. The results showed students' enthusiasm, especially regarding the discussion of